POLUSI UDARA AKIBAT AKTIVITAS KENDARAAN BERMOTOR DI JALAN PERKOTAAN PULAU JAWA DAN BALI - Nanny Kusminingrum; G. Gunawan (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Development of urban traffic volume has reached 15% per year. Transportation is a mayor cause of air pollution, 70% of air pollution is generated from vehicle exhausts. Air pollution parameters from motor vehicles such as carbon monox ide (CO), Nitrogen oxide (NOX), Methane (CH4), Non Methane (NonCH 4), Sulfur dioxide (SOx) and Paticulate (SPM 10) contribute heavily to global warming. Monitoring result of air pollution in urban roads such as Surakarta, Yogyakarta, Semarang, Surabaya, Denpasar (Bali), and Serang (Banten), and other cities passed by North Coast Road links showed that the air quality in this area nearly the limit line or standard air quality ambient especially Nitrogen oxide (NOx), suspended particulate matter (SPM10) and hydrocarbon (HC). The range of air quality ambient for CH 4 : 1,0 â€“ 1,97 ppm, NonCH4 : 1,5 â€“ 3,78 ppm, NOx: 0,06 â€“ 0,490 ppm, SOx: 0,001 â€“ 0,276 ppm, CO : 0,01 -11,53 ppm and particulate (SPM 10): 6,0 â€“ 260 ug/m3. According to Ministerial decree of Environment no. 45/1997. monitoring result with air pollution index (ISPU) showed that the condition was categorized â€œmoderateâ€ which mean the air quality will not affect on human health or animals, but can damage plants and aesthetics-value. Some correctives and measures to minimize air pollution are as follow : a.Consideration and application policy with environment regulations become important steps to the whole cycle road-projects. b.Social participation in environmen tal management as vehicle owners,road user and community of road environment. c. utilization of and environmental fuel and vehicles. d. The application of air pollution reduction technology such as landscape arrangement by restoration of vegetation. Key words : air pollution, vehicle, urban